AMOC, Water Mass Transformations, and Their Responses to Changing Resolution in the Finite‐VolumE Sea Ice‐Ocean Model. (23rd December 2020) - Sidorenko, Dmitry; Danilov, Sergey; Fofonova, Vera; Cabos, William; Koldunov, Nikolay; Scholz, Patrick; Sein, Dmitry V.; Wang, Qiang
Abstract: The Atlantic meridional overturning circulation (AMOC) is one of the most important characteristics of an ocean model run. Using the depth ( z ) and density frameworks, we analyze how the sinking and diapycnal transformations defining the AMOC as well as AMOC strength and variability react to mesh refinement from low to higher resolution in two model runs driven by the CORE‐II forcing. Both runs can represent the key locations of sinking and diapycnal transformations behind AMOC, that is, northeastern North Atlantic. Although their spatial patterns do not change significantly with resolution in both frameworks as the consequence of the same atmospheric forcing, the quantitative differences, reaching several sverdrups, are seen in different locations between two model runs for both frameworks. In particular, the refinement leads to the strongest differences in the vertical transport and diapycnal transformations in the latitude range between 30°N and 55°N. The z framework emphasizes the role of localized upwelling around the Gulf Stream separation site, whereas the density framework emphasizes the contribution of (spurious) diapycnal mixing around the Grand Banks. Both effects are reduced in the higher‐resolution run, leading to higher AMOC south of 26°N as compared to the low‐resolution run, despite the AMOC maxima, located at high latitudes, are higher in the low‐resolution run. We suggest that both AMOC frameworks should be used routinely in standard analyses, including forthcoming intercomparison projects. Plain Language Summary: In various international programs such as the Climate Model Intercomparison Project (CMIP), climate models are used to assess the past, present, and future climate. The Atlantic meridional overturning circulation (AMOC) is one of the most important characteristics of an ocean model simulation. Commonly, it is computed as a stream function of zonally averaged flow along the constant depth (z‐AMOC). However, there are shortcomings related to the inclination of density surfaces in reality, which may lead to the appearance of artificial circulation cells. In order to eliminate these artifacts, it is essential to compute the AMOC along constant density surfaces (ϱ‐AMOC). That is why recent studies underlined the importance of the ϱ framework for the AMOC analysis. However, neither the CMIP data nor the native output of most of the ocean circulation models is sufficient for the straightforward computation of ϱ‐AMOC. Hence, ϱ‐AMOC remains important but rarely computed diagnostics. In this paper we analyze the fundamental differences between both representations of AMOC in order to better understand the role of the spatial resolution of numerical models in representing AMOC formation, strength, and variability. We suggest that the ϱ‐AMOC and water mass transformation framework should be used routinely in standard analyses, including forthcoming intercomparison projects. Key Points: AMOC in depth and density coordinates manifests same physics differently Stronger interior transformation at low model resolution causes the difference in AMOC to high resolution FESOM, a representative of ocean climate models, is able to adequately simulate the locations of sinking and diapycnal transformations behind AMOC